Crystal structure of N′-((1-hydroxycyclohexyl)(phenyl)methyl)-2-methoxybenzohydrazide ethanol solvate, C23H30N2O4 - Guo Yamin; Gao Yanrong; Tang Wenqiang (Zeitschrift für Kristallographie - New Crystal Structures)
C23H30N2O4, monoclinic, P21/n (no. 14), a = 9.9661(6) Å, b = 18.5076(14) Å, c = 11.9817(9) Å, β = 97.489(3)°, V = 2191.2(3) Å3, Z = 4, R gt(F) = 0.0678, wR ref(F 2) = 0.2198, T = 298 K.